Sekularisasi Etika dan Krisis Moral Masa Kini: Secularisation of Ethics and Contemporary Moral Crisis - A. Harris, Khalif Muammar (Afkar: Jurnal Akidah dan Pemikiran Islam, 2021)
Secularisation of ethics is one of the dimensions of secularism that gives a direct impact on man’s way of life. Secularism as a philosophical program that began hundreds of years ago in Europe provided a materialistic and hedonistic parameter to measure human development and happiness. This study highlights the effects of modern moral philosophy, in particular Kantianism, utilitarianism, and emotivism, upon contemporary moral crises. It refuted the claim of the proponents of the secularisation of ethics that religion, particularly the belief in God, is not essential in morality. The failure of modern Western ethics in providing a universal and effective ethical theory has led to the marginalisation of ethics in all aspects of life. The secularisation of ethics which brings about deconsecration of values has negated God’s authority and affirmed man’s autonomy to decide on moral values, resulting in the dissolution of absolute moral standards and universal moral values. This research, therefore, reiterates the central role of Divine ethics and specifically Islamic ethics in providing universal and absolute moral obligations which has the capacity to save mankind from the perils of ethical relativism and moral bankruptcy.